Accelerating Climate Change Adaptive Capacity Through Regional Sustained Assessment and Evaluation in Hawai‘i and the U.S. Affiliated Pacific Islands - Keener, Victoria W.; Grecni, Zena N.; Moser, Susanne C. (Frontiers in Climate, 2022)
As the impacts and risks from climate change increase, the climate assessment landscape has expanded in scope and application, resulting in the desire for more information relevant to local decision-making. Some regions lack detailed climate projections and a body of consensus findings about sector-specific impacts, and there is a need for actionable, culturally-cognizant, translated climate information suitable for integration into operations and management, budgeting, funding proposals, and domestic and international policy. The Pacific Islands Regional Climate Assessment, or PIRCA, is the subject of this decade-long case study illustrating the need, development, and benefit of creating and sustaining a nuanced, collaborative, and deliberately inclusive climate assessment effort among researchers and practitioners in Hawaiʻi and the US-Affiliated Pacific Islands (USAPI). Using external evaluations done in 2013 and 2021, and our observations as participants in the process, we describe regional adaptive capacity challenges—an important component of the decision context for PIRCA stakeholders—and analyze the role of the PIRCA network in accelerating climate adaptation. We also examine how regional and national assessments complement each other, and how assessment processes can aid in translation to sub-national decision making across the climate science-policy interface. Results reveal components of the PIRCA that are foundational to its effectiveness: framing climate information in human and decision-centric ways; use of inclusive and non-extractive methods; willingness to shift approaches to meet stakeholder objectives; leveraging the resources of the Pacific Regional Integrated Sciences and Assessments (RISA) and other boundary organizations; taking the time to build relationships; and creating a dedicated position to sustain collaborations and relationships within the region and at larger assessment scales. Our experience and the feedback received through the evaluation suggest that these lessons are transferable to other regions and scales, and that sustained and collaborative regional climate assessments can serve a key function in complementing major national and international assessments, by translating and more effectively targeting information to meet local needs in support of regional climate adaptation and policymaking.